The Digital Dionysus: Nietzsche and the Network-Centric Condition - Mellamphy, Dan; Biswas Mellamphy, Nandita (punctum books, 2016)
Can Nietzsche be considered a thinker of media and mediation, as the German media theorist Friedrich Kittler declared in his influential book Gramophone, Film, Typewriter? Nietzsche was a truly transdisciplinary thinker, one who never fit into his own nineteenth-century surroundings and who recognized himself as a "herald and precursor" of the future, of our globally-reticulated digital present. Perhaps not since Kittler has there been a study - let alone an anthology - that re-assesses and re-evaluates Nietzsche's thought in light of the technically mediated and machinic conditions of the human in the age of digital networks.